1998
DOI: 10.1103/physrevlett.80.61
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Character of Stress Transmission in Granular Packings

Abstract: The correlation between contact forces and the texture of a packing of rigid particles subject to biaxial compression is analyzed by means of numerical simulations. Four different aspects are investigated: stress tensor, dissipation due to friction, angular distribution of forces, and fabric tensor characterizing the anisotropy of the texture. All of them provide evidence that the contact network can be decomposed unambiguously into two subnetworks with complementary mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
528
2
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 769 publications
(575 citation statements)
references
References 10 publications
(11 reference statements)
40
528
2
5
Order By: Relevance
“…However, even a linear chain of strong particles would not be stable against buckling without the participation of the particles that lie alongside them [23]. Therefore, it is necessary to develop techniques that do not include a minimum threshold force to be able to consider a particle to be part of a network.…”
Section: Introductionmentioning
confidence: 99%
“…However, even a linear chain of strong particles would not be stable against buckling without the participation of the particles that lie alongside them [23]. Therefore, it is necessary to develop techniques that do not include a minimum threshold force to be able to consider a particle to be part of a network.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the longitudinal force rule, the new shape is easily found to be a catenary, as realized by Hooke [15], and emphasized by Edwards [8]. On the other hand, a general body force can be supported, in three dimensions, if there are several different orientations of force chain, possibly forming a network or "granular skeleton" [7,11,17,18]. A minimal model for this is:…”
Section: Two Types Of Fragilitymentioning
confidence: 99%
“…1 (b)). Applying a similar argument to the intermediate axis leads to the ansatz that all three directors lie along principal stress axes; this is perhaps the simplest model in 3-d. One version of this argument links force chains with the fabric tensor [11], which is then taken coaxial with the stress [18].…”
Section: Fixed Principal Axis (Fpa) Modelmentioning
confidence: 99%
“…It was found that the forces have a nearly decreasing exponential distribution. Numerical simulations by the CD method provided detailed evidence for force chains, the organization of the force network into strong and weak networks, and the exponential distribution of strong forces [13,14]. Moreover, the force probability density functions (pdf's) from simulations showed that the weak forces (below the average force) in a sheared granular system have a nearly uniform or decreasing power law shape in agreement with refined carbon paper experiments [2,5].…”
Section: Introductionmentioning
confidence: 52%
“…The observed shape of force pdf's is unique in two respects: (1) the exponential part reflects the presence of very large forces in the system often appearing in a correlated manner in the form of force chains; (2) the nonvanishing category of weak forces, with a fraction of more than 60% of contact forces below the average force, means that the stability of force chains is ensured by a large number of vanishingly small forces [14,15]. The large number of contacts transmitting very weak forces is a signature of the arching effect.…”
Section: Dry Granular Mediamentioning
confidence: 99%